APPLICATION OF VERTICAL GRADIENT METHODS OF MICROGRAVITY TIME FUNCTION TO DETERMINE GROUND WATER REDUCTION IN SEMARANG PERIOD OF 2013 - Khumaedi, K.; Supriyadi, S.; Pradana, A.; Imam, S.; Yusuf, M.; Sarkowi, M. (Jurnal Pendidikan Fisika Indonesia, 2015)
The development of Semarang city requires the availability of water for daily use and industry in line with population growth. Uncontrolled use of water will damage the groundwater system. The purpose of this study was to determine the zone of the decrease of water level to obtain information about area that utilizes excess water. The method used is a micro-gravity vertical gradient between times. Gravity measurements were done at 124 points spread evenly between May and October 2013. The results showed that there was a decrease in ground water level in the Industries area Kaligawe, Tanah Mas, and Tlogosori which was identified with the vertical gradient anomaly of micro gravity between the times from May to October 2013. The regions which have high negative changes in ground water level (1.2-1.4 m / year) were the monitoring wells Madukoro 2, LIK Kaligawe and PT Aquaria which are the industrial areas. Exploitation of ground water in industrial areas is relatively high compared to the other regions.Perkembangan kota Semarang yang menuntut ketersediaan air untuk keperluan sehari-hari dan industri seiring dengan pertambahan jumlah penduduk. Pemanfaatan air yang tidak terkendali akan menyebabkan sistemÂ  air tanah rusak. Tujuan penelitian ini adalah menentukan zona penurunan muka air tanah untuk memperoleh informasi daerah yang memanfaatkan air secara berlebihan. Metode yang digunakan adalah gradien vertikal gaya berat mikro antar waktu. Pengukuran gaya berat di lakukan di 124 titik yang tersebar merata pada periode Mei dan Oktober 2013. Hasil peneltian menunjukkan telah terjadi penurunan muka air tanah di lingkungan Industri Kecil Kaligawe, perumahan Tanah Mas, Perumahan Tlogosori yang ditandai dengan anomali gradien vertikal gaya berat mikro antar waktu Mei-Oktober 2013. Wilayah yang memiliki perubahan muka air tanah negative tinggi (1,2-1,4 m/tahun), berada di sekitar sumur pantau Madukoro 2, LIK Kaligawe dan PT Aquaria dimana tutupan lahan di sekitar sumur pantau tersebut merupakan kawasan industri. Eksploitasi air tanah pada kawasan industri relatif tinggi jika dibandingkan dengan kawasan lainnya.Â